2018
DOI: 10.5194/cp-14-1035-2018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of sediment flux to a bathyal continental margin section through the Paleocene–Eocene Thermal Maximum

Abstract: The response of the Earth system to greenhousegas-driven warming is of critical importance for the future trajectory of our planetary environment. Hyperthermal events -past climate transients with global-scale warming significantly above background climate variability -can provide insights into the nature and magnitude of these responses. The largest hyperthermal of the Cenozoic was the Paleocene-Eocene Thermal Maximum (PETM ∼ 56 Ma). Here we present new high-resolution bulk sediment stable isotope and major e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…During PETM initiation, release of 0.3–1.1 PgC yr –1 of carbon as greenhouse gases to the ocean–atmosphere system 46 drove 4–5 °C of global warming 7 over a short period (<20,000 years) 5,810 . Although the North Atlantic Igneous Province (NAIP) LIP and the PETM are closely coincident in time 1113 , the rate and duration of NAIP carbon emissions have not yet been reconciled with the <20 kyr onset of PETM climate change 8,9,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…During PETM initiation, release of 0.3–1.1 PgC yr –1 of carbon as greenhouse gases to the ocean–atmosphere system 46 drove 4–5 °C of global warming 7 over a short period (<20,000 years) 5,810 . Although the North Atlantic Igneous Province (NAIP) LIP and the PETM are closely coincident in time 1113 , the rate and duration of NAIP carbon emissions have not yet been reconciled with the <20 kyr onset of PETM climate change 8,9,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…We employ an inverse modeling technique to produce nCIEs wherein the isotopic signature of the surface ocean dissolved inorganic carbon pool (δ 13 C DIC) is forced to follow a prescribed δ 13 C evolution, while an internal algorithm determines how much atmospheric CO 2 input with a specified isotopic signature is necessary to match this profile (Cui et al 2011, Cui et al 2013, Kirtland Turner and Ridgwell 2013, Dunkley Jones et al 2018. We choose to force surface DIC δ 13 C rather than atmospheric CO 2 δ 13 C because the former is a closer approximation to data from marine carbonates.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…carbon release over longer timescales that approach the residence time of carbon in the exchangeable reservoir, it becomes crucial to account for feedbacks such as carbonate compensation and rock weathering. More recently, modeling approaches have been utilized that explicitly consider the timing of a nCIE derived from sedimentary age models (Cui et al 2011, Cui et al 2013, Gutjahr et al 2017, Dunkley Jones et al 2018 in calculating the mass of carbon required to generate a particular nCIE.…”
Section: Introductionmentioning
confidence: 99%
“…The Bighorn Basin orbital chronology is broadly consistent with onset duration estimates based on an age model that assumed dynamic sedimentation as a function of the depositional environment [ 49 ]. Similarly, independent cyclostratigraphy on a shallow marine section from the paleo-Tethys at Zumaia demonstrated that the majority of the PETM CIE occurred within approximately 5 kyr with the remainder occurring over a single precession cycle [ 50 ]. By contrast, tuning using Fe counts across a PETM section from Spitsbergen in the Svalbard Archipelago suggested the onset of the PETM CIE in bulk marine organic carbon occurred gradually over a full precession cycle [ 51 ].…”
Section: History Of Paleocene–eocene Thermal Maximum Onset Duration Ementioning
confidence: 99%
“…My focus is particularly on the onset duration of the PETM, so I focus on just the duration over which carbon is emitted in these scenarios (approx. 70 kyr maximum) and exclude the representation of enhanced removal of 13 C-depleted carbon that could account for the relatively rapid recovery in δ 13 C following the body of the CIE [ 9 , 50 , 63 ]. I add one further PETM carbon input scenario for comparison to the existing published scenarios (dark blue lines in figure 4 ): this combines short onset duration (3 kyr) for the input of isotopically depleted carbon (δ 13 C = −35‰) with an extended interval (70 kyr) of elevated rates of volcanic outgassing (δ 13 C = −6‰).…”
Section: Comparison Of Paleocene–eocene Thermal Maximum Onset Scenarimentioning
confidence: 99%